Traffffiic Noiise Effffectts on tthe Effffiiciiency off Teachiing and Sttudyiing Cllassrooms - Modhhi, Khalid Hmoud; Ismail, Aodai Abdulillah (Nahrain University College of Engineering Journal, 2017)
Traffic noise is unpleasant sounds generated due to vehicles and pedestrians activities. Its effect on the efficiency of teaching and studying classrooms continuously increases. That is because of the population growth, vehicles ownership increasing, scientific development, and urbanization process, which leads to variety of traffic noise sources and increasing the generated noise level Students opinion at fifteen different classrooms is used to investigate the traffic noise effectiveness on the teaching and studying classrooms efficiency. Different characteristics of students, and survey with questions of short answer and multiple-choice are selected for this aim. Level of generated traffic noise from both vehicles and pedestrians was measured inside some classrooms to study its relation with some characteristics of both vehicles and pedestrians. Also this study shows some of suitable treating manners to mitigate the traffic noise and increase the teaching and studying classrooms efficiency.